Comparison of the properties of standard soil and aquatic fulvic and humic acids based on the data of differential absorbance and fluorescence spectroscopy. (December 2020) - Liu, Siqi; Benedetti, Marc F.; Han, Weiqing; Korshin, Gregory V.
Abstract: This study compared effects of pH, ionic strength and complexation with Mg 2+ on the chromophores and fluorophores of aquatic and terrestrial NOM exemplified by the standard isolates Suwannee River fulvic and humic acid (SRFA and SRHA) and Pahokee Peat fulvic and humic acids (PPFA and PPHA) provided by the International Humic Substance Society (IHSS). The intensity of the differential spectra of the NOM isolates increased monotonically with pH. These spectra comprised contributions of similar chromophore systems associated with the carboxylic and phenolic moieties. The intensity of SRFA and PPFA fluorescence changed non-monotonically vs. pH indicating that the deprotonation of the phenolic fluorophores decreased their emission yields. Examination of the effects of pH on the slopes of the log-transformed absorbance of NOM showed that the influence of deprotonation on the conformations of PPFA and PPHA molecules was less prominent than those for SRFA but not dissimilar to those of SRHA. Changes of the differential spectra and spectral slopes showed that Mg 2+ /PPFA and Mg 2+ /PPHA complexation was more effected by electrostatic interactions while the involvement of phenolic groups was notable for SRFA. The observed trends highlight similarities and differences in the properties of the chromophores and fluorophores in the standard isolates of soil and aquatic NOM. These results necessitate further systematic comparison of the properties of NOM isolates and those of unaltered NOM. Graphical abstract: Image 1